Epicuticular wax chemistry, morphology, and physiology in sand bluestem, andropogon gerardii ssp. hallii, and big bluestem, andropogon gerardii ssp. gerardii - Shelton, Jennifer (Kansas State University, 2012)
Plant epicuticular wax (ECW) isolates internal tissues from harsh external conditions increasing drought tolerance. Beta-diketone-rich ECW reflect light and result in a glaucous phenotype that may ameliorate the thermal environment of the leaf. The overall goal is to characterize the form and function of ECW in two closely related, but phenotypically divergent grasses. [italicized]Andropogon gerardii ssp. [italicized]gerardii, big bluestem, is a non-glaucous, agronomically and ecologically dominant grass in the United States while [italicized]Andropogon gerardii ssp. [italicized]hallii, sand bluestem, is a glaucous subspecies restricted to dry, sandy soils. The objectives are to contrast sand and big bluestem ECW chemistry, morphology, and physiology to determine the distinctions in ECW resulting in the glaucous phenotype and determine the effect this has on leaf optical qualities and permeability. Gas chromatography mass spectrometry (GC-MS) and scanning electron microscopy (SEM) were used to examine ECW chemistry and micromorphology. It was hypothesized that beta-diketones and beta-diketone tubules where present only in leaves of sand bluestem and that the ECW was more reflective and abundant and the cuticle was less permeable. Beta-diketones and tubular ECW were absent in big bluestem and common on sand bluestem’s surface, although less than 20% of ECW was beta-diketones. Functional implications of ECW phenotypes were investigated by comparing minimum conductance (G[subscript]min), wax load, reflectance, and transmittance. Reflectance, with and without ECW, and G [subscript]min were measured with an infrared gas analyzer and a spectroradiometer, respectively. Sand bluestem had twice the ECW in mg cm[superscript]2 (P=.01) and three times lower G [subscript]min in ms[superscript]-1 10[superscript]-5 (P=.02). Partial least squares (PLS) models were trained to predict subspecies from reflectance spectra and were able to distinguish the subspecies. These experiments indicate that in comparison to big bluestem, increased reflectance is a property uniquely imparted to sand bluestem by ECW and the presence of beta-diketones determines the distinction. Glaucous crop species have shown higher yield under drought and extreme weather, including drought, is expected to become more common. Therefore, this study of glaucous waxes, may be applied in engineering drought tolerance.
Keywords: β-diketone; Monocot adaptation; Epicuticular wax; Leaf reflectance; Andropogon; Cuticle; Biology (0306)